Adubação nitrogenada e inoculação com Azospirillum brasilense na cultura do milho para grão e silagem - Tonin, Tiago João (2016)
In view of the use of corn for various purposes, principally for animal feed in the form of silage or grain to make animal feed, this work aimed to evaluate the effects of nitrogen fertilization in different doses (0, 60, 120, 240 and 480 kg h N-¹) in the form of urea, in association of different purposes hybrids and inoculated with Azospirillum brasilense strains Ab-V5 and Ab-V6. Were evaluated the development, plant silage productivity, nutritional value, morphological structure and grain yield. The experimental area was carried out in two agricultural crops, 2013/2014 and 2014/2015, sowed in October, harvest for silage at the end of January and early February and grain harvest in March, in both years. Inoculation with A. brasilense increased silage productivity (dry matter per area), improved the dry matter content at ensiling, increased the corn cob contents in the silage, decreased the hemicelulose content and ash and increased the buffering capacity of forages. The inoculation had interaction with hybrids used increasing their productivity and changing the stem percentage ensiled. Fertilizations from 120 kg ha-¹ N are enough to potentially raise the productivity of the crop for silage and combined with hybrids of silage purposes are more appropriate, as the largest biomass productivity without significant changes in the silage quality. For grain yield, significant interaction between inoculation with A. brasilense and AS 1572 hybrid was founded, increasing grain production (1 ton ha-¹) and it was associated with the increment in number of grains per cob. The hybrid with grain production purpose, the AG 9030, showed higher grain mass, compared to hybrids with mixed purposes, AS 1572. Nitrogen fertilization increased the crop yield by raising the grain weight. Inoculation caused no effects on the external morphological structure of plants.